Giardia spp. promote the production of antimicrobial peptides and attenuate disease severity induced by attaching and effacing enteropathogens via the induction of the NLRP3 inflammasome. Issue 4 (April 2020) - Manko-Prykhoda, Anna; Allain, Thibault; Motta, Jean-Paul; Cotton, James A.; Feener, Troy; Oyeyemi, Ayodele; Bindra, Sunint; Vallance, Bruce A.; Wallace, John L.; Beck, Paul; Buret, Andre G.
Graphical abstract: Highlights: We examined mechanisms whereby Giardia spp. protect against attaching and effacing enteropathogen infections. Giardia reduces A/E pathogen-induced colitis by inducing antimicrobial peptide (AMP) production. Disease modulatory mechanisms in co-infected mice are Nod-like receptor pyrin-containing 3 (NLRP3)-dependent. Elevated levels of AMPs and bacterial killing in co-infected mice are NLRP3-dependent. Abstract: Polymicrobial infections of the gastro-intestinal tract are common in areas with poor sanitation. Disease outcome is the result of complex interactions between the host and pathogens. Such interactions lie at the core of future management strategies of enteric diseases. In developed countries of the world, Giardia duodenalis is a common cause of diarrheal disease. In contrast, giardiasis appears to protect children against diarrhea in countries with poor sanitation, via obscure mechanisms. We hypothesized that Giardia may protect its host from disease induced by a co-infecting pathogen such as attaching and effacing Escherichia coli . This enteropathogen is commonly implicated in pediatric diarrhea in developing countries. The findings indicate that co-infection with Giardia attenuates the severity of disease induced by Citrobacter rodentium, an equivalent of A/E E. coli in mice. Co-infection with Giardia reduced colitis, blood in stools, fecal softening, bacterial invasion, and weight loss; the protective effects were lost when co-infection occurred in Nod-like receptor pyrin-containing 3 knockout mice. In co-infected mice, elevated levels of antimicrobial peptides Murine β defensin 3 and Trefoil Factor 3, and enhanced bacterial killing, were NLRP3-dependent. Inhibition of the NLRP3 inflammasome in human enterocytes blocked the activation of AMPs and bacterial killing. The findings uncover novel NLRP3-dependent modulatory mechanisms during co-infections with Giardia spp. and A/E enteropathogens, and demonstrate how these interactions may regulate the severity of enteric disease.